Pengaruh Video Infografis terhadap Hasil Belajar Materi Keanekaragaman Hayati di SMA Negeri 1 Belimbing: (The Effect of Infographic Video on Learning Outcomes of Biodiversity Material at SMA Negeri 1 Belimbing) - Apriani, Resti; Rahayu, Hanum Mukti; Sunandar, Ari (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
This study aims to determine the differences in student learning outcomes at SMA Negeri 1 Belimbing on biodiversity material taught with infographic videos and determine the magnitude of the influence of infographic videos on biodiversity material on student learning outcomes at SMA Negeri 1 Belimbing. This study uses an experimental method with a form of quasi experimental research (Quasi Experimental Design) based on the research design of Nonequivalent Control Group Design. The samples in this study were class X2 as the experimental class and class X4 as the control class determined by simple random sampling technique. Based on the results of the study, the difference in student learning outcomes with the percentage of completeness of the experimental class posttest score was 90% and the control class was 51.613%. The results of the effect size calculation are 1,669 with a large percent nonoverlap of 73,4%, so it is included in the large category and there is an influence of infographic videos on biodiversity material on student learning outcomes at SMA Negeri 1 Belimbing. Abstrak. Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar siswa materi keanekaragaman hayati yang diajarkan dengan video infografis dan mengetahui besarnya pengaruh video infografis pada materi keanekaragaman hayati terhadap hasil belajar siswa di SMA Negeri 1 Belimbing. Penelitian ini menggunakan metode eksperimen dengan bentuk penelitian eksperimen semu (Quasi Experimental Design) berdasarkan rancangan penelitian Nonequivalent Control Group Design. Sampel pada penelitian ini yaitu kelas X2 sebagai kelas eksperimen dan kelas X4 sebagai kelas kontrol yang ditentukan dengan teknik simple random sampling. Berdasarkan hasil penelitian perbedaan hasil belajar siswa dengan persentase ketuntasan nilai posttest kelas eksperimen sebesar 90% dan kelas control sebesar 51,613%. Hasil perhitungan effect size yaitu sebesar 1,669 dengan besar percent nonoverlap sebesar 73,4% maka masuk dengan kategori besar dan terdapat pengaruh video infografis pada materi keanekaragaman hayati terhadap hasil belajar siswa di SMA Negeri 1 Belimbing.